2011
DOI: 10.1073/pnas.1019082108
|View full text |Cite
|
Sign up to set email alerts
|

Killer cell Ig-like receptor (KIR) 3DL1 down-regulation enhances inhibition of type 1 diabetes by autoantigen-specific regulatory T cells

Abstract: Both Foxp3 + regulatory T cells (Tregs) and antigen-expanded Foxp3 − Tregs play an important role in regulating immune responses as well as in preventing autoimmune diseases and graft rejection. Molecular mechanisms modulating Treg function remain largely unclear, however. We report here on the expression and function of an inhibitory killer cell Ig-like receptor, KIR3DL1, in a nonobese diabetic (NOD) mouse-derived autoantigen-specific Treg (2D2), which protects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Leishmania induced Tregs accumulate at the infection site and multiply in response to L. donovani [6]. Tregs are negatively regulated by KIR in type-1 diabetes [48]. KIR is inhibitory or activating, depending upon binding with its respective ligands [8,24,49].…”
Section: Ifn-γ Fitc →mentioning
confidence: 99%
“…Leishmania induced Tregs accumulate at the infection site and multiply in response to L. donovani [6]. Tregs are negatively regulated by KIR in type-1 diabetes [48]. KIR is inhibitory or activating, depending upon binding with its respective ligands [8,24,49].…”
Section: Ifn-γ Fitc →mentioning
confidence: 99%
“…Understanding the genetic and signaling mechanisms controlling the functional determination of these T cells should help maintain immune tolerance and suppression of self-tissue destruction by Tpaths. Comparative gene array analyses have shown that autoreactive Tpaths and Tregs express a distinct gene profile (10). The genes responsible for the functional determination of Tpaths vs. Tregs remain unclear, however.…”
mentioning
confidence: 99%
“…Another interesting set of experiments was done by Qin et al [43], who described the expression and function of the inhibitory killer cell immunoglobulinlike receptor KIR3DL1 in GAD-specific Tregs (2D2) derived from NOD mice. KIR3DL1 is a member of the KIR family, which plays an important role in regulating natural killer cell function.…”
Section: Regulatory T Cells: Not Always As Regulatorymentioning
confidence: 98%
“…Downregulation of KIR3DL1 was able to enhance the regulatory function of Tregs and their ability to inhibit insulitis and diabetes development in the NOD mouse. This receptor could be a new molecular target for the improvement of Treg functional potency and successful Treg-based cellular immunotherapy [43].…”
Section: Regulatory T Cells: Not Always As Regulatorymentioning
confidence: 99%